Implementing the Model of Specialized Education Based on the Principle of Distributed Responsibilities of Educational Cluster Participants; Advances in Social Science, Education and Humanities Research; Vol. 493: International Conference on Education Studies: Experience and Innovation (ICESEI 2020) - Astapova E. Elena (2020, 2020)
Title screen